'She just got me': supporting care experienced young people negotiating relationships and identities at school. (24th October 2021) - Macleod, Gale; Dallas‐Childs, Robin; Brough, Colin; Toye, Martin
Abstract : In this article we examine the complex relationship between care experience, mental health and exclusion from school and how young people (YP) negotiate these different experiences and identities. The study is a secondary analysis, informed by symbolic interactionist theory, of interviews conducted with 19 care experienced YP in Scotland. Not all of the YP were excluded and not all had a formal mental health diagnosis, as such our study design allows interrogation of the contexts and relationships which not only facilitate but also disrupt pathways to exclusion. It also allows reconsideration of assumptions of vulnerability which are often applied to care experienced YP. Our findings suggest that these YP are moving beyond 'role playing' the identities ascribed to them and actively seek out relationships which enable them to construct alternative identities.